Repositioning population and Reproduction Health for the attainment of National and Millenium Development Goals Investing in Population and Reproductive Health for better Welfare of Kenyans - Somayajulu, U. V. (Nairobi kenya association for the promotion and Development (NCAPD))
Contributed articles presented at the 31st Annual Conference of the Indian Association for the Study of Population, held at Sri Venkateswara University, during 3-5 November 2009.
section I. Population dynamics -- section II. Reproductive health : determinants and care -- section III. Methodological issues -- section IV. Miscellaneous.
Keywords: Reproductive health; Maternal health services; Communicable diseases; Medical policy